Total nnee replacement. Postacute phase in rehabilitation: objectives and strategies in postacute treatment - Cademartiri, C.; Soncini, G. (Acta Biomedica Atenei Parmensis, 2004)
Identification of a population with homogeneous characteristics is the fundamental introduction to elaborate a rehabilitation plan after operation of total knee arthroplasty (TKA). The main objectives of our rehabilitative protocol are: improvement of the preoperative clinical state, prevention and management of the common postoperative problems and complications. The first objective requires the improvement of the function of the operated knee (good articular excursion, muscular strengthening and recovery of ambulation and of gait pattern), as well as the reduction of pain. These protocol objectives are progressively achieved spreading postoperative rehabilitative strategies into four stages, during which patient should take instruction about the adoption of a correct life style.